2016
DOI: 10.1108/jfc-11-2015-0062
|View full text |Cite
|
Sign up to set email alerts
|

Causes, effects and deterrence of insurance fraud: evidence from Ghana

Abstract: Purpose This paper aims to measure the extent of effects of insurance fraud on the financial performance of insurance companies in Ghana. It also examines the causes and stringent measures that can be used to fight against insurance fraud. Design/methodology/approach Primary and secondary data obtained from 39 insurers in Ghana are used in this paper. A multiple regression model is used to determine the relationship between financial performance and insurance fraud variables. Findings The results from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…by the fraudsters with their own opinionated feelings or beliefs (Akomea-Frimpong et al, 2016) is found to be positively related to fraud among employees. Sunardi & Amin (2018) indicates that rationalization relates positively to employee fraud.…”
Section: H1: Pressure Affects Financial Statement Fraudmentioning
confidence: 93%
See 2 more Smart Citations
“…by the fraudsters with their own opinionated feelings or beliefs (Akomea-Frimpong et al, 2016) is found to be positively related to fraud among employees. Sunardi & Amin (2018) indicates that rationalization relates positively to employee fraud.…”
Section: H1: Pressure Affects Financial Statement Fraudmentioning
confidence: 93%
“…Likewise, Bonsu et al (2018) found weaker internal control, inadequate training and fraud policies as the major causes of fraud in the financial institutions in Ghana. Other studies affirm the assertion that internal control weaknesses can be major contributing factors for fraud to be committed (Akomea-Frimpong et al, 2016 andAsmah et al, 2020). According to Asmah et al (2020), inadequate controls in some areas of banks can fuel the commission of fraud among bank employees.…”
Section: H1: Pressure Affects Financial Statement Fraudmentioning
confidence: 95%
See 1 more Smart Citation
“…Supervisory capacity should be better than that supervised, so the authorities need to add experienced employees in finance. According to Isaac, Charles, & Dei (2016) [17], adequate training for insurance marketers is one way to prevent insurance fraud.…”
Section: Improve Reporting System Regulations To Improve Insurance Company Governancementioning
confidence: 99%
“…Therefore, the technology currently used should have or be equipped with strong security, because if it is used under certain conditions and with bad impetus by utilizing certain parties (Davis, 1989), then this will produce a conspiracy of users who have the motivation not good will be very detrimental to the organization. By preventing through inherent supervision of the use and use of information technology, corruption can be minimized and prevented (Tang 2018;Halbouni & Garbau;Akomea 2016;Quah;and Xin Li 2015;Bussell 2010;Shim & Eom 2009;and Bhatnagar 2003).…”
Section: The Influence Of Information Technology On the Causes Of Cormentioning
confidence: 99%